Menghidupkan Kembali Suara Perempuan : Adaptasi Teks-Teks Siti Rukiah Kertapati dalam Pertunjukan Api Kartini Edisi Khusus: Mencatat Kerja dan Pemikiran Perempuan oleh Mirat Kolektif - Mochammad Salman Alfaris; Wahyu Novianto; Tafsir Huda; Bagong Pujiono (Creativity And Research Theatre Journal, 2026)
This study examines the adaptation process of texts by Siti Rukiah Kertapati carried out by Mirat Kolektif in the performance Api Kartini Special Edition: Recording Women's Work and Thoughts. Siti Rukiah, as one of the editors of Api Kartini magazine in the 1960s, was an important figure in Indonesian feminist journalism and literature whose contributions are often overlooked in mainstream historiography. Mirat Kolektif adapted poems, short stories, and magazine columns from Siti Rukiah's book Tandus Siti Rukiah's book Tandus into a contemporary theater performance medium through a collaborative and multidimensional approach. This research uses a descriptive qualitative method with data collection techniques in the form of performance observation in-depth interviews with the creative team (director, scriptwriter, actors, and artistic director), and audio-visual documentation studies. The results of the research show that the adaptation was carried out through four main strategies: (1) transformation of the form from text to audio-visual performance; (2) compilation of historical and biographical narrative contexts; (3) reinterpretation of themes with a contemporary feminist approach; and (4) reconstruction of symbolic space through stage artistry. This adaptation is not merely a transfer of medium, but a cultural and political strategy to revive the voices of marginalized women, deconstruct patriarchal narratives, and strengthen the audience's critical awarenessof gender inequality. This performance becomes a form of living archive that connects